UZBEK REGIONAL PRESS: FROM THE JADIDISM ERA TO DIGITAL TRANSFORMATION - Rakhmatova, Sadoqat (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
This article explores the historical development of Uzbekistan’s regional press, tracing its evolution from the era of Jadidism to the contemporary stage of digital transformation. Regional newspapers and journals have played a crucial role in the socio-political life of society, as they represent the interests of local communities, address pressing social issues, and serve as an effective channel of communication between citizens and state institutions. The study identifies four main stages in the development of the regional press: the Jadid period, the Soviet period, the independence period, and the current era of digital transformation. During the Jadid era, the press functioned as an ideological tool of national awakening and enlightenment. In contrast, under the Soviet system, journalism was tightly controlled and primarily served as an instrument of propaganda. With the advent of independence, media freedom expanded, enabling the press to promote democratic values, national ideology, and cultural renewal. In the twenty-first century, the emergence of internet journalism and the rapid spread of social media have fundamentally reshaped regional journalism, providing immediacy, interactivity, and multimedia opportunities. The findings of the study highlight the functional features of regional media — delivering local news, shaping public opinion, promoting cultural and educational values, and ensuring dialogue between society and the state — as highly significant for both media theory and practice. The research emphasizes that the regional press should be studied not only as part of historical development but also as a relevant phenomenon of modern communication systems. This dual perspective makes it possible to understand the role of regional journalism in the age of globalization and digital transformation, where it functions as both an information source and a platform for democratic participation.
Keywords: regional press; Jadidism; Soviet period; independence; digital transformation; journalism; communication